Factors Associated with the Non-Adherence of TB Screening in Children Aged - Lidwina Vania Shaynaputri; Anindita Soetadji; Dea Amarilisa Adespin; Stefani Candra Firmanti (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Background: TB screening in children having close contact with smear-positive TB patients is urgent to conduct to improve the case detection rate and to achieve the “End TB” target. In fact, the implementation of screening in Indonesia is still inadequate.Objective: To analyze the factors associated with the non-adherence of TB screening in children aged <15 years with smear-positive TB patients’ close contact.Methods: A cross-sectional study was conducted in Semarang between February and August 2020. Subjects were children <15 years old with smear-positive TB patient's close contact. Data were collected from interviewed parents or guardians of the child using a structured questionnaire. Chi-square or Fisher's exact test analysis was used to identify the factor associated with non-adherence to TB screening in children.Results: A total of 84 children were recruited into this study. The proportion of children who did not undergo the screening is still high (86,9%), and there was a significant association with children's age (OR 13,556, 95% CI=3.135-58,613), parents' age (OR 41,143, 95% CI=4,025-420,604), parents’ education level (OR 0,114, 95%CI=0.027–0.477), distance to health facilities, knowledge level, perceived barriers, and cues to action. There was no significant association between children’s gender, economic level, perceived threats with non-adherence of screening.Conclusion: Children and parents’ age, education level, distance to health facilities, knowledge level, perception of barriers, and cues to action associated with the non-adherence of TB screening in children aged <15 years with smear-positive TB patients’ close contact.